Rationality criteria for Galois extensions - Matzat, Bernd Heinrich (Galois Groups over ℚ, 1989)
Some rationality criteria for finite Galois extensions overℂ(t)are explained. The first rationality criterion and the second rationality criterion, together with the corresponding examples are contained in the forthcoming lecture notes [27] (see also [23—25]). The rationality criteria in sections 4 and 5, the braid orbit theorem, and the twisted braid orbit theorem, are new. With the last one, the Mathieu group M24 is realized as Galois group over ℚ.